Pattern of Cardiovascular Diseases in Diabetic population - a seven year study in a tertiary care hospital of Bangladesh - Irfan, SM Rezaul; Habib, Samira Humaira; Hoque, Shabnam Jahan; Mohibullah, AKM (Bangladesh Critical Care Journal, 2020)
Background: Cardiac involvement in diabetes covers a wide spectrum, ranging from asymptomatic silent ischemia to clinically evident heart failure. The total number of people with diabetes is projected to rise from 171 million in 2000 to 366 million in 2030. Up to 80% of diabetic patients die of macrovascular complications, including coronary artery disease (CAD), stroke, and peripheral vascular disease (PVD). CVD is the single-most important contributor, and is responsible for 17% of total mortality. Because of the growing numbers of diabetic patients and the increased mortality after their first cardiovascular event, it is critical to identify and treat risk factors early and aggressively in these patients. Methodology: This is a retrospective observational study carried out in the Department of Cardiology BIRDEM General Hospital Dhaka Bangladesh from 2011 to2017. Total 5598 patients who were admitted to the institute between 2011 to 2017 was studied and evaluated to see the pattern of cardiovascular diseases in diabetic population. Results: Among total 5598 patients, 50.02% were male and 49.98% were female. Majority of them were Diabetic and Hypertensive. Most of the patient having cardiovascular disease belongs to age 50-70 years. IHD was found among 1810(32.33%) patients with slightly male predominance. Different types of Cardiomyopathy were found among 330(5.8%) study population. Heart failure of different forms were present among 632 (11.28%) of patients. Different types of Arrhythmia were found among 159 (2.8%) of admitted patient. Rheumatic Vulvular Heart disease were found 64 (1.1%) of individual. Congenital Heart disease were found among 51 with ASD 36 (70.58%) followed by VSD 15 (29.42%) and PAD in 105 (1.8%). Conclusion: This study reflects the higher incidence of Ischemic Heart Disease and higher association of Hypertensive Heart Disease in Diabetic population mostly affecting the 50-70 year age groups. This observational study also shows that the duration of hospital stay has gradually declined over the course of seven years. The incidence of Cardiomyopathy, Peripheral Vascular Disease and Heart Failure could be different in Diabetic population if wide range multicenter prospective approach would have been applied. Bangladesh Crit Care J September 2020; 8(2): 96-101